PENERAPAN MODEL PBL BERBANTUAN MEDIA ULTAMERASI UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI DAN MINAT BELAJAR MATEMATIKA - Maulidar Maulidar; Indah SuryaWati (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The aim of this research is to determine the increase in numeracy literacy skills and interest in learning mathematics in class V students at SD 53 Banda Aceh by applying the Problem Base Learning (PBL) model assisted by ULTAMERASI media. The design used in this research was Quasi Experimental Pretest-Posttest Control Group Design. From the research results, the pre-test and post-test results showed that the normalized gain (N-Gain) of students' numeracy literacy abilities was sig. (2-tailed) N-Gain score of 0.039 is less than 0.05. And based on the analysis of the results of the pre-test and post-test questionnaires regarding students' interest in learning mathematics, it was found that the normalized gain (N-Gain) had a value of Sig. (2-tailed) = 0.031. Thus, it can be concluded that there is a difference between the average N-Gain of numeracy literacy abilities and interest in learning mathematics taught using the Problem Base Learning (PBL) learning model assisted by snake and ladder numeracy media (ULTAMERASI) and the average N-Gain of numeracy literacy abilities and students' interest in learning mathematics taught using conventional learning. If we look at the average N-Gain value of the experimental class and control class, it is found that the N-Gain value of the experimental class is higher than the control class, so it can be concluded that the increase in the ability to understand numeracy literacy in the experimental class is better than the control class